Հանդուրժողականության արդի ըմբռնման ակունքները. կրոնական հանդուրժողականություն - Տ . Ա . Փիրումյան (ՀՀ ԳԱԱ հրատ.)
Концепция толерантности наиболее тщательно была разработана английским философом Дж. Локком. Именно поэтому многие считают его создателем концепции толерантности. The concept of tolerance in thorough manner was developed by English philosopher J. Lock. That is why many consider him the founder of the concept of tolerance.
Keywords: B Philosophy; Psychology; Religion; B Philosophy; BL Religion